PENGEMBANGAN METODE PEMBELAJARAN BERBASIS RUQYAH SYAR'IYYAH UNTUK PENINGKATAN KEMAMPUAN SPIRITUAL SISWA DI SD MUHAMMADIYAH 17 SURABAYA - Shafwan, Muhammad Hambal; Mahmudin, Thoriq (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2024)
The background of this research is that Ruqyah syar'iyyah is an alternative in increasing students' spiritual abilities. The aims of this study were first to find out insights about ruqyah syar'iyyah at SD Muhammadiyah 17 Surabaya, second, to find out the development of ruqyah syar'iyyah-based learning methods at SD Muhammadiyah 17 Surabaya, third, to find out the factors that support and hinder students' spiritual abilities at SD Muhammadiyah 17 Surabaya through the development of ruqyah syar'iyyah-based learning methods. This researcher is a qualitative research, the data sources used are data sources and samples at SD Muhammadiyah 17 Surabaya, the techniques used in data collection are observation, interviews and documentation, and the method used in data analysis is descriptive qualitative. The results of the study found that (1) the understanding of the meaning of ruqyah syar'iyyah at SD Muhammadiyah 17 Surabaya is well known to students. (2) The ruqyah method used is the lecture, demonstration and discussion method. (3) The supporting factors of the ruqyah syar'iyah therapy conducted at SD Muhammadiyah 17 Surabaya are the strong will of the students and support from the family, while the inhibiting factor is the lack of remembrance of Allah.